Dimethyl sulfoxide: a substance with pleiotropic effects actual in musculoskeletal diseases - D. Yu. Ivkin; S. V. Okovity; A. S. Ivkina; N. A. Anisimova (Лечащий Врач)
Dimethyl sulfoxide which is known since the end of XIX century, has a number of important pharmacological effects. This is an antioxidant, a substance with antimycotic and antimicrobial effects, cryoconservant, analgesic and anti-inflammatory drug, diuretic, vasodilatator. Analgesic and anti-inflammatory activities are performed also due to influence on NLRP3-inflamasomes and cytokines, as well as properties of penetrant and enhancer, make dimethyl sulfoxide attractive for treatment of musculoskeletal diseases.